La autoregulación de la emoción y el rendimiento académico en el aula: El rol del docente - Gargurevich, Rafael (2015)
In order to recognize if the learning experience has been effective, one must explore different variables related to the learning process and to the demonstration of what has been learned (academic achievement). One variable that clearly relates with these two events are emotional experiences. Emotions are psychological processes that intervene with the learning process as well as the students’ academic achievement, either to favor or impair them. (Shunck, Pintrich y Meece, 2008; Gumora y Arsenio, 2002). This article discusses the nature of the emotional experience as well as the consequences of emotional self-regulation in the learning process and in academic achievement. Also, it discusses how the teacher can help students achieve an self-regulated emotional behavior (Shunck, Pintrich y Meece, 2008). In this way, it is said that emotions can favor or interfere with the cognitive processes that are associated with learning and with academic achievement. Finally, it comments on the results of diverse investigations related with the topic of classroom performance and its relationship with emotional self-regulation. (Benbenutti, McKeachie y Lin, 2002, Graziano, Reavis, Keane y Kalkins, 2007; Hamre, & Pianta, 2001;Vuorela, & Nummenmaa, 2004).